Study of Aquaculture Water Quality for Tilapia (Oreochromis niloticus) in the Aquaponic System at the Deju Farm Hatchery Unit - Yonarta, Danang; Madhat Husayn, M.; Azhari, Muhammad; Anggana Rarassari, Madyasata (Journal Of Artha Biological Engineering, 2023)
Tilapia (Oreochromis niloticus) is well known by freshwater fans, both in developing and developed countries. Utilization of space as much as possible can be an effort to increase the productivity of the cultivation activities carried out. The aquaponic system is a combination of aquaculture (fish farming) and hydroponic plant cultivation in one place. The basic principle of aquaponics is that it can be done at the same time by utilizing fish manure and fish food scraps as a source of nutrition for cultivated plants. The purpose of this activity is to provide information about the utilization of the aquaponic cultivation system and its effect on water quality while rearing tilapia is maintained. This research has been carried out at UPR Deju Farm which is located Jl. Mazmu, Indralaya Raya, Kec. Indralaya in October-November 2022. This activity used a comparative experiment consisting of P1 (kale plant), P2 (spinach plant), and P3 (lettuce plant). The results showed that the P1 treatment (kale plant) was the best treatment which produced temperatures ranging from 27-31°C, pH 7-8, dissolved oxygen 2.3 mg L-1, ammonia 0.098-0.290 mg L-1, and salinity 9.29 ppt, absolute length growth was 3.2 cm, absolute weight was 2.1 g, survival was 84%, and kale plant growth was 8.3 cm.